2020
DOI: 10.1007/s11538-020-00718-x
|View full text |Cite
|
Sign up to set email alerts
|

Speed Switch in Glioblastoma Growth Rate due to Enhanced Hypoxia-Induced Migration

Abstract: We analyze the wave-speed of the Proliferation Invasion Hypoxia Necrosis Angiogenesis (PIHNA) model that was previously created and applied to simulate the growth and spread of glioblastoma (GBM), a particularly aggressive primary brain tumor. We extend the PIHNA model by allowing for different hypoxic and normoxic cell migration rates and study the impact of these differences on the wave-speed dynamics. Through this analysis, we find key variables that drive the outward growth of the simulated GBM. We find a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…These parameters were chosen as they represent the tumor's response to hypoxic stress. In previous work, we have observed that all of these parameters (except for β) influence the outward growth rate of PIHNA simulations, which is another consideration of the effects of hypoxia on GBM [12]. We note that the varying tumor kinetics (migration rates D c , D h and proliferation rate ρ) affect the nodularity of the simulated tumors.…”
Section: Virtual Experimentsmentioning
confidence: 69%
See 4 more Smart Citations
“…These parameters were chosen as they represent the tumor's response to hypoxic stress. In previous work, we have observed that all of these parameters (except for β) influence the outward growth rate of PIHNA simulations, which is another consideration of the effects of hypoxia on GBM [12]. We note that the varying tumor kinetics (migration rates D c , D h and proliferation rate ρ) affect the nodularity of the simulated tumors.…”
Section: Virtual Experimentsmentioning
confidence: 69%
“…The effect of an increase in D h /D c is more pronounced for tumors that are more sensitive to the hypoxic environment caused by the ischemia, see Appendix Figures 9 -11. In previous work, we have shown that an increase in D h /D c increases the outward growth rate of PIHNAsimulated GBM [12]. With faster hypoxic migration rates, the simulated tumor cell densities are able to travel through the hypoxic region faster.…”
Section: Faster Hypoxic Cell Migration Rates Promote Distant Recurrencementioning
confidence: 75%
See 3 more Smart Citations